Concurrent validity of the athla velocity application for measuring tennis service ball velocity - BALIKCI, MURAT (My University, 2023)
Aim: To analyse the validity of the mobile application (Athla Velocity) used to measure ball speed. Method: A total of 67 volunteer male tennis players with a mean age of 24.94 ± 4.91 years participated in the study. In all measurements, the successful 10 service strike velocity made by the athletes in the determined area were evaluated. Each service strike was measured concurrently using both the Stalker Solo 2 radar device and the Athla Velocity application. Bland-Altman and regression analyses were used to determine the validity. Results: A high positive correlation was found between the radar device and Athla Velocity Application measurements (ICC = 0.970, r2 =.989). In addition, according to the Bland-Altman analysis, the measurement results of the two methods were found to be within the calculated limited area to a large extent. Conclusion: It has been determined that the Athla Velocity application can measure 98% close to the Stalker Pro 2 device in ball velocity measurement. As a result, it can be said that the Athla Velocity application can be used validly in ball velocity measurements.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Athla Velocity App; Ball velocity; Gun radar; Performance analysis of sport; Tennis; Performance analysis of sport; Tennis; Ball velocity; Gun radar; Athla Velocity App